2012
DOI: 10.5603/fhc.2012.0060
|View full text |Cite
|
Sign up to set email alerts
|

Use of X-ray microprobe to diagnose bone tissue demineralization after caffeine administration

Abstract: Abstract:Caffeine is a methylxanthine which permeates the placenta. In studies on animals, it has been shown to produce teratogenic and embryotoxic effects in large doses. The objective of this study was to assess the influence of caffeine on the development of bone tissue, with particular reference to elemental bone composition using an X-ray microprobe. The research was conducted on rats. The fertilized females were randomly divided into an experimental and a control group. The experimental group was given c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…However, mineralisation could be also analysed using atomic absorption spectroscopy, but the method is rarely applied since it needs expensive equipment and gives only quantitative results [24]. For a long time it was the only method that allowed direct measurement of various elements concentration, but presently such data can be also obtained with mMR [4] or special X-ray microprobe [28]. On the other hand, usefulness of MR is also limited especially in highly mineralised structures, due to low signal in both principal T1-and T2-weighted images [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mineralisation could be also analysed using atomic absorption spectroscopy, but the method is rarely applied since it needs expensive equipment and gives only quantitative results [24]. For a long time it was the only method that allowed direct measurement of various elements concentration, but presently such data can be also obtained with mMR [4] or special X-ray microprobe [28]. On the other hand, usefulness of MR is also limited especially in highly mineralised structures, due to low signal in both principal T1-and T2-weighted images [4].…”
Section: Discussionmentioning
confidence: 99%
“…Some apparatus allow also examination of skeletal morphology and the method is called a morphometric X-ray absorptiometry [13,28,29]. However, due to incompatibility with pups of small laboratory animals that is a consequence of low resolution power, it has been used only in late postnatal studies or for pups obtained from large laboratory animals, e.g.…”
mentioning
confidence: 99%
“…Caffeine intake is negatively associated with gestational changes in animals, such as lower rates of fertilization and embryonic implantation, low birth and placental weight, greater number of stillbirths, increased expression of apoptotic markers and altered placental and bone formation [9,27,[40][41][42][43][44][45][46] ( Table 1).…”
Section: Caffeine and Pregnancymentioning
confidence: 99%
“…Olchowik and colleagues [45] reported that 30 mg/day of caffeine intake during pregnancy had negative influence in female rats' bone tissue. Tomaszewski and colleagues [41], using X-ray microprobe to examine female rats fetuses treated with 30 mg/day of caffeine, observed that the decreased bone mineralization was dominant in the treated group.…”
Section: Caffeine Intake During Pregnancy: What Are the Real Evidences?mentioning
confidence: 99%
“…Since then, a number of studies have confirmed the negative effect of high doses of caffeine ingested during pregnancy both for the mother and the developing foetus [2,3,7,15,16,18,22,25,27,30,31].…”
Section: Introductionmentioning
confidence: 99%